Analysis of National Health Insurance Towards A Universal Health Insurance - Andi, Ferry Afi (Badan kebijakan Fiskal, 2015)
As the implementation of Indonesian constitutional duty to provide the right for social security for all citizens, government of Republic of Indonesia provides the national health insurance program since January 1st 2014 which is operated by BPJS Kesehatan. The national insurance program is aimed to be a universal health insurance. There are some aspects that need to be analyzed to make this health insurance system to be a universal health insurance. Using meta analysis and to compare the implementation and the expected result of the program using secondary data obtained from previous iteratures, This research is trying to look at the prospect of national health insurance to be a universal health insurance. The reasearh found that the concept of National Health System has already met the criteria of a universal health insurance. However, the implementation of the concept still needs to be improved . The government needs to set a mechanism to accelerate and to ensure the participation of the people the program. Besides that the infrastructure of health service facilities need to be improved to ensure the provision of health care to the participants. The significance of this research is to bring some outlook that can be considered for improvement of the national health insurance program